2016
DOI: 10.1080/00071005.2016.1184742
|View full text |Cite
|
Sign up to set email alerts
|

Support for School-to-school Networks: How Networking Teachers Perceive Support Activities of a Local Coordinating Agency

Abstract: External support by a local coordinating agency facilitates the work of school-to-school networks. This study provides an innovative theoretical framework to analyse how support provided by local education offices for school-to-school networks is perceived by the participating teachers. Based on a quantitative survey and qualitative interview data from a networking project in eight German districts, we argue that in order to enable networks to work independently on innovative reforms, local coordinating agenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These and equivalent reviews (e.g. Brown, 2020;Penuel and Gallagher 2017;Sartory et al 2017;Mintrop 2016;Bryk 2015;and Suggett, 2014) suggest that networking policies and practices are developing most clearly in Anglo-Saxon, European, and Latin American contexts. However, the fact that most published evidence is weighted towards these contexts does not mean that educational networks are not a feature of policy and practice in other parts of the world.…”
Section: Network Around the Worldmentioning
confidence: 99%
“…These and equivalent reviews (e.g. Brown, 2020;Penuel and Gallagher 2017;Sartory et al 2017;Mintrop 2016;Bryk 2015;and Suggett, 2014) suggest that networking policies and practices are developing most clearly in Anglo-Saxon, European, and Latin American contexts. However, the fact that most published evidence is weighted towards these contexts does not mean that educational networks are not a feature of policy and practice in other parts of the world.…”
Section: Network Around the Worldmentioning
confidence: 99%
“…These studies emphasize the constructive role of peer-to-peer feedback on instructional methods, although collaboration can also be focused on goal setting (cf. Sartory, Jungermann, & Järvinen, 2016). Muijs et al (2011), for example, studied the drivers of successful collaborative partnerships between UK primary schools and found that intensive involvement in actual joint projects and joint "development of teaching and learning approaches" were particularly crucial (p. 576).…”
Section: The Mediating Effect Of Downward Networking In An Educationamentioning
confidence: 99%
“…Inter-school partnerships, collaborations and networks have been promoted in education as mechanisms for sharing knowledge and expertise, improving pupil outcomes, addressing equity challenges, making schools more responsive to parental and community needs, and/or securing wider innovations (Hargreaves, 2012;Leithwood, 2019;Paniagua & Istance, 2018;Rincon-Gallardo & Fullan, 2016;Sartory et al, 2017;Suggett, 2014). Evidence that networks impact in the ways that their proponents claim is growing, but remains far from comprehensive (Armstrong et al, 2020;De Lima, 2010).…”
Section: Introductionmentioning
confidence: 99%